TEACHING CULTURALLY RESPONSIVE PEDAGOGY IN MULTILINGUAL CLASSROOMS: VALUING LINGUISTIC AND CULTURAL DIVERSITY - Putera, Zulmy Faqihuddin; Akid, Akid (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2022)
Multilingual and multicultural classrooms have become a significant challenge for educators due to increasing cultural and linguistic diversity. The purpose of this study is to explore the importance and methods of implementing culturally responsive pedagogy in multilingual classrooms. The study used a descriptive literature research approach to explore the importance and methods of implementing culturally responsive pedagogy in multilingual classrooms. The finding reveal that acknowledging and valuing linguistic and cultural diversity in education not only enriches the learning environment but also prepares students to thrive in a global society, making it essential for educators to embrace culturally responsive pedagogy as a fundamental practice in their teaching. By fostering an inclusive atmosphere that respects and celebrates differences, educators can enhance students' sense of belonging and self-efficacy, which research has shown is crucial for fostering engagement and motivation across diverse populations in multilingual settings, ultimately resulting in improved academic performance and holistic well-being.